Study about photoinduction-based technology for trapping small brown planthopper - Zhan, Shaoqi; Sheng, Zhentao; Liu, Yiming; Xu, Ke; Wang, Jiahui; Cao, Weixing; Tian, Yongchao; Ni, Jun (Frontiers in Plant Science, 2022)
To provide a theory to guide the selection of the illumination parameters of light emitting diode (LED)-based light sources used for trapping Laodelphax striatellus, we used LED light sources and devices built in-house to detect L. striatellus phototactic behavior. Through phototaxis screening experiments of different light sources and the comparative experimental method, we analyzed the response patterns of L. striatellus to wavelength, light intensity, layout, flash frequency of monochromatic light sources, as well as combined color light sources, and discussed the mechanisms of the phototactic behavior of L. striatellus under different light sources. The results of the monochromatic light experiment showed that the trapping rate of the L. striatellus to the linear blue light source of 460 nm was the highest and was also significantly affected by the light intensity. The results of the experiments with the combined color light sources showed that compared with the linear 460 nm blue light source, the trapping rate of the L. striatellus was significantly improved by the polychromatic light, and the blue–green light led to the best improvement, reaching 1.5 times that of the trapping rate in the case of monochromatic light sources. The wavelength composition, light intensity, shape, and flash frequency of the light source used in this study can provide a theoretical basis for the development of LED-based light traps specifically for L. striatellus.